Studies on Some Sooty Moulds on Guava In Malaysia - Kwee, Lim Tong (1988)
Sooty moulds proliferate in abundance on the foliage of guava, subsisting on the honeydew secreted by scale insects aphids, white flies, and mealy bugs. Nine species, five Ascomycetes species namely, Phragmocapnias betel, Scorias philippensis, Trichomerium grandisporum, Limacinula musicola and Aithaloderma clavatisporum; and four Deuteromycetes genera viz. Tripospermum sp., Polychaeton sp., Leptoxyphium sp. and Conidiocarpus sp., are described and reported as new records on guava for Peninsular Malaysia.